2017
DOI: 10.1155/2017/2481961
|View full text |Cite
|
Sign up to set email alerts
|

The Great Impostor: Transaminitis Masking the Coinfection of Syphilis and Human Immunodeficiency Virus

Abstract: Introduction. The incidence of syphilis continues to rise in the United States over the past 15 years. This disease process is classified into stages and may present with a coinfection of Human Immunodeficiency Virus (HIV). Case Report. We present a case of a 32-year-old African American male who presented with cutaneous manifestations of secondary syphilis and transaminitis. A workup revealed that the transaminitis was secondary to underlying syphilitic hepatitis in the presence of HIV coinfection. The patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…The most common stage that causes abnormal liver enzymes is secondary syphilis. It is estimated that 3% of secondary syphilis cases can present as syphilitic hepatitis, but among all the patients with syphilis, hepatitis occurs in 0.2% to 3% of patients [3,4]. A literature review of 97 cases by Huang et al in 2018 demonstrated that the most common clinical manifestations of syphilitic hepatitis were rash (78%), fatigue/poor appetite (57%), icterus (35%), fever (26%), weight loss (23%), abdominal pain (22%), phallodynia (13.4%), sore throat (8.2%), and headache 7.2%.…”
Section: Discussionmentioning
confidence: 99%
“…The most common stage that causes abnormal liver enzymes is secondary syphilis. It is estimated that 3% of secondary syphilis cases can present as syphilitic hepatitis, but among all the patients with syphilis, hepatitis occurs in 0.2% to 3% of patients [3,4]. A literature review of 97 cases by Huang et al in 2018 demonstrated that the most common clinical manifestations of syphilitic hepatitis were rash (78%), fatigue/poor appetite (57%), icterus (35%), fever (26%), weight loss (23%), abdominal pain (22%), phallodynia (13.4%), sore throat (8.2%), and headache 7.2%.…”
Section: Discussionmentioning
confidence: 99%
“…The first recognized case of hepatitis attributable to syphilis was reported in 1585 and termed “luetic jaundice” [4]. While syphilitic hepatitis has since been an established diagnosis in the medical literature as a component of secondary syphilis, it is not a commonly encountered etiology in patients seen for transaminitis, much less clinical hepatitis [5].…”
Section: Discussionmentioning
confidence: 99%
“…Liver involvement in secondary syphilis is especially prevalent in patients with concurrent HIV infection, likely due to similar risk factors and degree of immunosuppression [2, 8]. The notable high rates of coinfection can be attributed to parallel risk factors including unprotected sexual activity, men who have sex with men, and intravenous drug use [4]. The most current CDC STD treatment guidelines emphasize the importance of routine HIV screening in all patients who pursue evaluation and therapy for any STDs [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La afectación hepática es un compromiso poco habitual de la sífilis primaria y secundaria, descrita en aproximadamente 0,2-3%, siendo más frecuente en pacientes VIH, ya que comparten factores de riesgo similares 5,6 .…”
unclassified